If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3x + -13 = 7(x + -9) Reorder the terms: -13 + x + 3x = 7(x + -9) Combine like terms: x + 3x = 4x -13 + 4x = 7(x + -9) Reorder the terms: -13 + 4x = 7(-9 + x) -13 + 4x = (-9 * 7 + x * 7) -13 + 4x = (-63 + 7x) Solving -13 + 4x = -63 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -13 + 4x + -7x = -63 + 7x + -7x Combine like terms: 4x + -7x = -3x -13 + -3x = -63 + 7x + -7x Combine like terms: 7x + -7x = 0 -13 + -3x = -63 + 0 -13 + -3x = -63 Add '13' to each side of the equation. -13 + 13 + -3x = -63 + 13 Combine like terms: -13 + 13 = 0 0 + -3x = -63 + 13 -3x = -63 + 13 Combine like terms: -63 + 13 = -50 -3x = -50 Divide each side by '-3'. x = 16.66666667 Simplifying x = 16.66666667
| 4x+15-9x=19-17x+12x-4 | | 18/840 | | 13x=5x | | 9000=x^2-18x+56 | | 4x^2+2x+3+[-2x]+6= | | -56=-8x+7 | | 2x+17-9x=20-18x+11x-3 | | -9+9*3= | | (2x-3y)+(x+3y)=180 | | 6x-4=6+4x | | 12x^3+16x^2-28x=0 | | (3/8)/(2/3)=24 | | 5w(12w+1)+12w+1= | | (2x^2+3x-54)/(x^2-5x+6)=0 | | (2x^2+3x-54)/(x^2-5x+6) | | 8000=x^2-18x+56 | | g(3)=9+5 | | 9n-19=5+n | | a+3=-11 | | 4x-5(1-2x)=6(x+3) | | 5(4x+2)=250 | | -3*3-9*-3= | | (3/8)/(2/3) | | -4=-4(-m-2) | | (64a^3*b^-6)^2/3 | | (64a^3b^-6)^2/3 | | x^3-2x-1=0 | | 2(-x+3)+5x= | | -3(4x-6)+8x=-6 | | 28=3-5x | | 6(15.2)+20=y | | 10x^2+[-2]+3x^2+5x+5= |